Visualization of Flows in Curved Channels with a Moderate or High Rotation Speed - Liqiu Wang; K. C. Cheng (International Journal of Rotating Machinery)
Flows in channels with streamwise curvature and spanwise rotation are visualized in terms of end-view near the exit of the test sections through injecting smoke into the flows. Two test sections are used, i.e. the rectangular channels with the aspect ratio of and 10, respectively. The work focuses on visualization of Dean and Coriolis vortices under the effects of secondary instabilities and flows in the region with a relatively high rotation speed. The results show that the secondary instabilities cause the Dean and Coriolis vortices oscillating in various forms and the flows at high rotation speeds are controlled by the secondary instabilities rather than the primary instability. In particular, the secondary instabilities lead the flows to be unsteady and turbulent somewhat like the bursting flow in the turbulent boundary layers.